Imaging of Bone Tumors and Tumor-Like Lesions Techniques and Applications - Davies, A. Mark.; Sundaram, Murali.; James, Steven L. J. (Medical Radiology, 2009)
This is a comprehensive textbook that provides a detailed description of the imaging techniques and findings in patients with benign and malignant bone tumors. In the first part of the book, the various techniques and procedures employed for imaging bone tumors are discussed in detail. Individual chapters are devoted to MRI, CT, nuclear medicine, and interventional procedures. The second part of the book gives an authoritative review of the role of these imaging techniques in diagnosis, surgical staging, biopsy, and assessment of response to therapy. The third part of the book covers the imaging features of each major tumor subtype, with separate chapters on osteogenic tumors, cartilaginous tumors, etc. The final part of the book reviews the imaging features of bone tumors at particular anatomical sites such as the spine, ribs, pelvis, and scapula. Each chapter is written by an acknowledged expert in the field, and a wealth of illustrative material is included. This book will be of great value to musculoskeletal and general radiologists, orthopedic surgeons, and oncologists.